Anti-HIV-1 Effect of the Fluoroquinolone Enoxacin and Modulation of Pro-Viral hsa-miR-132 Processing in CEM-SS Cells - Verena Schlösser; Helen Louise Lightfoot; Christine Leemann; Seyedeh Elnaz Banijamali; Aathma Merin Bejoy; Shashank Tiwari; Jeffrey L. Schloßhauer; Valentina Vongrad; Andreas Brunschweiger; Jonathan Hall; Karin J. Metzner; Jochen Imig (Non-Coding RNA)
Background: Despite tremendous advances in antiretroviral therapy (ART) against HIV-1 infections, no cure or vaccination is available. Therefore, discovering novel therapeutic strategies remains an urgent need. In that sense, miRNAs and miRNA therapeutics have moved intensively into the focus of recent HIV-1-related investigations. A strong reciprocal interdependence has been demonstrated between HIV-1 infection and changes of the intrinsic cellular miRNA milieu. This interrelationship may direct potential alterations of the host cells’ environment beneficial for the virus or its suppression of replication. Whether this tightly balanced and controlled battle can be exploited therapeutically remains to be further addressed. In this context, the fluoroquinolone antibiotic Enoxacin has been demonstrated as a potent modulator of miRNA processing. Here, we test the hypothesis that this applies also to selected HIV-1-related miRNAs. Methods: We studied the effect of Enoxacin on HIV-1 replication coupled with miRNA qRT-PCR analysis of HIV-1-related miRNAs in CEM-SS and MT-4 T-cells. The effects of miRNA mimic transfections combined with Enoxacin treatment on HIV-1 replication were assessed. Finally, we employed an in vitro DICER1 cleavage assay to study the effects of Enoxacin on a pro-HIV-1 miRNA hsa-miR-132 processing. Results: We established that Enoxacin, but not the structurally similar compound nalidixic acid, exhibits strong anti-HIV-1 effects in the T-cell line CEM-SS, but not MT-4. We provide experimental data that this effect of Enoxacin is partly attributed to the specific downregulation of mature hsa-miR-132-3p, but not other tested pro- or anti-HIV-1 miRNAs, which is likely due to affecting DICER1 processing. Conclusions: Our findings show an anti-retroviral activity of Enoxacin at least in part by downregulation of hsa-miR-132-3p, which may be relevant for future antiviral therapeutic applications by modulation of the RNA interference pathway.